An RF‐gated wireless power transfer system for wireless MRI receive arrays. Issue 4 (14th February 2018) - Byron, Kelly; Robb, Fraser; Stang, Pascal; Vasanawala, Shreyas; Pauly, John; Scott, Greig
Abstract: In MRI systems, cable‐free receive arrays would simplify setup while reducing the bulk and weight of coil arrays and improve patient comfort and throughput. Since battery power would limit scan time, wireless power transfer (WPT) is a viable option to continuously supply several watts of power to on‐coil electronics. To minimize added noise and decouple the wireless power system from MRI coils, restrictions are placed on the coil geometry of the wireless power system, which are shown to limit its efficiency. Continuous power harvesting can also cause a large increase in the background noise of the image due to diode rectifier up‐conversion of noise around the frequency of the transmitted power. However, by RF gating the transmitted power off during the MRI receive time while continuing to supply power from a storage capacitor, WPT is demonstrated to have minimal impact on image quality at received power levels up to 11 W. The integration of WPT with a 1.5T scanner is demonstrated.